Assessment of Analgesic Effects of Paracetamol Alone and Diclofenac + Paracetamol in Patients Undergoing Dental Extraction - Alam, Dr. Khushnud; Pratap Singh, Dr. Himanshu; Gokkulakrishnan, Dr. S. (International Journal Of Drug Research And Dental Science, 2025)
Aim: To assess and compare the analgesic efficacy of paracetamol alone and diclofenac + paracetamol combination in patients undergoing dental extraction. Materials and Methods: An open-label, randomized trial was conducted on 180 patients (20–50 years) allocated into two groups, with postoperative pain assessed using the Numerical Rating Scale (NRS) at immediate, day 1, and day 3 intervals. Results: Both regimens reduced pain, but diclofenac + paracetamol showed significantly lower NRS scores on day 1 and day 3 (p < 0.001), with no reported complications in either group. Conclusion: While paracetamol is effective for mild pain, diclofenac + paracetamol provides superior relief for moderate to severe pain post-extraction, without additional adverse effects.